Mechanically deposited tungsten disulfide saturable absorber for low-threshold Q-switched erbium-doped fiber laser - Lau, Kuen Yao; Abd Latif, Amirah; Abu Bakar, Muhammad Hafiz; Muhammad, Farah Diana; Omar, Muhammad Firdaus; Mahdi, Mohd Adzir (Springer, 2017)
In this paper, we report a Q-switched erbium-doped fiber laser incorporating tungsten disulfide (WS2) as the saturable absorber. A direct mechanical deposition technique using a scotch tape is employed to place the WS2 powder onto the tip of a fiber ferrule. Several runs of mechanical extraction are performed to reduce the thickness of WS2 powder on the fiber tip. The fabricated WS2 saturable absorber exhibits a saturation intensity of 548.6 MW/cm2, modulation depth of 4.1% and non-saturable loss of 67.8%. A ring cavity erbium-doped fiber laser integrating the WS2 saturable absorber yields continuous wave lasing and Q-switching threshold at pump power of 10 and 12.7 mW, respectively. This Q-switching pump power threshold is the lowest to the best of the authors’ knowledge. The proposed technique of direct mechanical deposition is inexpensive, significantly faster and simpler compared to previously reported methods.